Assessing myxozoan presence and diversity using environmental DNA. Issue 12 (November 2016) - Hartikainen, Hanna; Bass, David; Briscoe, Andrew G.; Knipe, Hazel; Green, Andy J.; Okamura, Beth
Graphical abstract: Highlights: Environmental DNA (eDNA) reveals diversity across the myxosporean phylogeny in water and faecal samples. A custom barcoding approach amplifies myxosporean small subunit rDNA that is missed in 'eukaryote-wide' surveys. Piscivore activities integrate myxozoan infections in prey over broad spatial scales. Recommendations for assessing the presence of myxozoans in eDNA are provided. Abstract: Amplicon sequencing on a High Throughput Sequencing platform (custom barcoding) was used to detect and characterise myxosporean communities in environmental DNA samples from marine and freshwater environments and in faeces of animals that may serve as hosts or whose prey may host myxosporean infections. A diversity of myxozoans in filtered water samples and in faeces of piscivores (otters and great cormorants) was detected, demonstrating the suitability of lineage-specific amplicons for characterising otherwise difficult to sample parasite communities. The importance of using this approach was highlighted by the lack of myxosporean detection using commonly employed, broadly targeted eukaryotic primers. These results suggest that, despite being frequently present in eDNA samples, myxozoans have been generally overlooked in "eukaryote-wide" surveys. Lineage-specific primers, in contrast, detected 107 operational taxonomic units that were assigned to both the "freshwater" and "marine" myxosporean lineages. Only 7% of these OTUs clustered with sequences in GenBank, providing evidence for substantial undescribed myxosporean diversity. Many new operational taxonomic units, including those found in otter faeces, clustered with a clade of myxosporeans previously characterised by sequences from invertebrate hosts and water samples only. Because myxozoan species identification is heavily reliant on molecular signatures, lineage-specific amplicon sequencing offers an effective and non-destructive means of improving our knowledge of myxozoan diversity. In addition, the analysis of myxozoan DNA in faeces of piscivores offers a potentially efficient method of sampling for diversity and revealing life cycles as piscivore activities may integrate myxozoan infections in fish over relatively broad spatial scales.